Early initiation of breast feeding in baby friendly hospital initiative set up - how feasible is it? - Sharma, Utpal; Pathak, Giridhar; Baruah, Rupali (International Journal Of Community Medicine And Public Health, 2016)
Background: The baby friendly hospital initiative (BFHI) was started in India in 1993. Under this, the hospital with maternity services, have to follow the ten steps to successful breastfeeding. The World Health Organization also recommends early initiation of breastfeeding. IMNCI strategy recommended systematic assessment of breastfeeding and emphasized counseling of mothers. Breast feeding in India is universal, but the initiation of breast feeding is late. Objectives: To assess the pattern of breast feeding in a baby friendly hospital initiative setup. Methods: A cross sectional study was conducted among 209 post-partum women of aged 18-35 years delivered in Obstetrics and Gynaecology Department, Guwahati Medical College. Analysis of collected data was done using software Epi Info 7, Chi-square test and percentages. Results: It was observed that only 5.26% women initiated breast feeding within one hour, of which majority 3.38% were illiterate (p<0.05). Late initiation of breast feeding was high amongst mothers (42.1%) kept too long under observation. Most of the Primiparous (55.98%) knew about the advantage of early and exclusive breast feeding than Multiparus (24.88%), which was statistically significant (p<0.05). 80.86% women had received antenatal counseling on breastfeeding but only 58.85% knew that exclusive breastfeeding should be continued for 6 months. Conclusions: Awareness on early initiation of breastfeeding was low despite most of the women received antenatal counseling on breastfeeding. Single strategies, such as providing breastfeeding support or written materials to women or educating health professionals, are unlikely to increase breast feeding initiation as stand-alone measures.